Extracting Tweets Using R in The Context of Ethical Issues - Mohamed Najid, Mohamad Hafizuddin; Zulkifli, Zahidah; Othman, Roslina; Rokis, Rohaiza (IEEE, 2021)
Twitter is a well-known social networking platform where users exchange information and express opinions. Since many people’s interactions now take place on social media, this medium has rapidly become a source of capturing knowledge from users. The aim of this study is to find tweets using R that are then related to Ibn Khaldun’s thoughts. The analysis was carried out with a simple algorithm written in R Programming. 45 keywords based on Ibn Khaldun’s thoughts were constructed as the hashtag to retrieve data from Twitter. As a result of the data extraction, 1075 public tweets were collected through the search API. The simple algorithm is capable to facilitating the process of extracting data from Twitter, such that it easily known to the public tweets that exist in a given time period and this can be used as reference material for further development process. For further work, it is possible to use text mining activities and sentiment analysis approaches, as well as explore various social media platforms using R packages for decision makings